Word‐finding difficulties in Parkinson's disease: Complex verbal fluency, executive functions and other influencing factors. Issue 3 (9th February 2022) - Hedman, Eli; Hartelius, Lena; Saldert, Charlotta
Abstract: Background: Persons with Parkinson's disease (PD) frequently report word‐finding difficulties. Many of the established tests are, however, insufficient in detecting mild cases of such symptoms. Results from earlier research have suggested that controlled oral word association tests (COWATs) with high demands on cognitive processing resources could prove helpful in detecting the more subtle (language‐related) problems seen in neurological disorders such as PD. Aims: First, to examine whether persons with PD (PwPD) differ in performance on different types of COWATs compared with non‐brain‐damaged controls. Second, to investigate possible relationships between executive functions and the novel complex oral semantic fluency (COSEF) task performance scores in the PwPD group. Third, to investigate whether age, years of education, severity of motor symptoms and self‐perceived severity of word‐finding difficulties influenced the COSEF task results. Methods & Procedures: A total of 17 PwPD participated in the study. Their results were compared with a matched control group ( n = 17) at both group and individual levels. One phonemic and two types of semantic COWATs were used. Correlations between the COSEF task and executive function results, age, education and severity of motor symptoms were analysed in the PwPD group. Outcomes & Results: The PwPD group had significantly lower scores on the COSEF task compared with the control group, but not on the other COWATs. A variation in the results was seen on an individual level. In the PwPD group, large significant correlations were seen between the COSEF task and verbally based tasks measuring working memory and cognitive flexibility. Both age and education, but neither self‐perceived severity of word‐finding difficulties nor motor symptoms, were correlated with the COSEF task result in the group of PwPD. Conclusions & Implications: The results are in line with the predictions that a relatively more cognitive demanding COWAT such as the COSEF task could prove valuable when assessing word‐finding difficulties in PD in research and clinical assessment. What this paper adds: What is already known on the subject: Varying degrees of word‐finding difficulties are a common symptom in PD and may affect everyday communication. Discreet word‐finding difficulties can be hard to detect with the established language assessment tools. What this paper adds to existing knowledge: This study adds insights into how PwPD perform on different types of COWATs compared with a control group. It also sheds light on the relationships between a novel, more cognitive complex COWAT and executive functions in PD. What are the potential or actual clinical implications of this work?: More cognitively complex COWATs can contribute significantly to the assessment of discreet word‐finding difficulties, but it is important to include a thorough anamnesis regarding language and communication in PwPD.